POST-9/11 TRAUMATIC PARANOIA AS REFLECTED IN DON DELILLO’S FALLING MAN - Siti Kurniati Rasad; Achmad Munjid (Rubikon : Journal of Transnational American Studies, 2019)
This article investigates how the trauma of 9/11 tragedy affects the lives of the characters in DeLillo’s Falling Man and shows how the trauma of 9/11 portrayed in the novel reflects American collective trauma. This investigation is qualitative research utilizing memory and trauma as the theoretical framework. The discussion in this article reveals that individual experience the trauma of 9/11 tragedy differs from one person to another. While other characters go through their mourning successfully, the main character in the novel becomes a perennial mourner and is ceaselessly haunted by his traumatic memory due to constant avoidance from his trauma. His continuous externalization of his trauma causes him to focus on the external threats and becomes a paranoiac. On a societal level, American society is also perpetually mourning and is haunted by post-traumatic paranoia continuously. American exceptionalism, biased orientalist perspective about the orient, and alleged prolonged quasi war between Islam and the west have framed the collective experience of the trauma in binary opposite narrative of a good versus evil war. The collective trauma perpetuates and many policies are born out of their paranoia.Keywords: 9/11 tragedy; memory; mourning; post-traumatic paranoia; trauma